2003
DOI: 10.2486/indhealth.41.158
|View full text |Cite
|
Sign up to set email alerts
|

Immunotoxicological Effects of Agent Orange Exposure to the Vietnam War Korean Veterans.

Abstract: Immunomodulatory effects of 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) demonstrated using animals are thymic atrophy, downregulation of cytotoxic T or B lymphocyte differentiation or activation, whereas human immunotoxicities have not been investigated well. This study was undertaken to evaluate overall immunologic spectrum of the Vietnam War Korean veterans exposed to Agent Orange contaminated with TCDD. Quantity of red blood cells, hemoglobin and hematocrit in the veterans suffered from chronic diseases asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 36 publications
1
28
0
Order By: Relevance
“…Two more recent reports also failed to demonstrate any induction of ANA in Japanese subjects intoxicated with TCDD [78] and in Koreans veterans exposed to Agent Orange [79]. A 2004 study showed that secondary immune responses to influenza viral pathogens were likely to be influenced by TCDD exposures occurring prior to or at the time of primary infections, as measured by virus-specific Ig levels, while secondary responses were only temporarily suppressed.…”
Section: Effects Of Environmental Estrogens On the Immune Systemmentioning
confidence: 99%
“…Two more recent reports also failed to demonstrate any induction of ANA in Japanese subjects intoxicated with TCDD [78] and in Koreans veterans exposed to Agent Orange [79]. A 2004 study showed that secondary immune responses to influenza viral pathogens were likely to be influenced by TCDD exposures occurring prior to or at the time of primary infections, as measured by virus-specific Ig levels, while secondary responses were only temporarily suppressed.…”
Section: Effects Of Environmental Estrogens On the Immune Systemmentioning
confidence: 99%
“…Yu et al (1998) found elevated prevalence of influenza and Chang et al (1982) bronchitis in these subjects. Effects on immune markers were also seen in Koreans exposed to Agent Orange in Vietnam (Kim et al 2003). however pointed out that in the Yu-Cheng cohort e.g.…”
Section: Immune Effectsmentioning
confidence: 91%
“…However, a non-significant decrease in most lymphocyte subsets was reported among the high-exposed group. Another study among Vietnam War Korean veterans conducted by Kim et al (2003) showed lower plasma IgG levels as compared to controls, with a significant decrease in the IgG1 levels. In contrast, increased plasma levels of IgE were observed among exposed veterans.…”
Section: Studies On Vietnam War Veterans Exposedmentioning
confidence: 99%